Insect (Hexapoda) diversity in the oceanic archipelago of Fernando de Noronha, Brazil: Lauxaniidae (Diptera) - Soares, Matheus M. M.; Gaimari, Stephen D.; Corrêa-Neto, José De J.; De-Oliveira, Francisco Limeira-; Rafael, José A. (Zootaxa, 2024)
The Lauxaniidae fauna from the oceanic Archipelago of Fernando de Noronha, Brazil is revised. Three genera and four species are recognized: Camptoprosopella equatorialis Shewell, 1939, Pachyopella flavida (Wiedemann, 1824), Poecilominettia erebus Soares & Gaimari, sp. nov. and Poecilominettia octovittata (Williston, 1896). In addition, we provided an illustrated key and high-resolution photographs of external morphology and male and female terminalia of species. Finally, we present the first insights into the effects of climate variables on the abundance of the species analyzed.